New teaching strategies from student teachers' pedagogical conceptual change in CALL. (June 2020) - Yang, Yu-Fen; Kuo, Nai-Cheng
Abstract: Previous studies rarely explored the involvement of student teachers in using computer-assisted language learning (CALL) to generate new strategies for future teaching. This longitudinal study involved ten student teachers in a CALL teacher training program where they experienced pedagogical conceptual change and created new teaching strategies to solve teaching problems in CALL classrooms. The student teachers' study reports, feedback on the development of online systems, collaborative dialogues from system meetings, and a semi-structured interview were analyzed by content analysis, showing the changes of the ten student teachers' pedagogical concepts toward teaching strategies. Three main pedagogical conceptual changes emerging from these student teachers include: (1) creating new CALL teaching strategies to support students' learning in overcoming difficulties in learning English as a foreign language; (2) obtaining new experiences in applying CALL knowledge into teaching practice and system improvement; (3) engaging in role reversal among teachers, system designers, learners, and facilitators. This study suggests that the breakthrough of CALL teacher education involves student teachers in switching perspectives and roles and engaging in collaborative and experiential learning to generate insights for new teaching strategies in a life-long learning process.